A fundamental change emerging in locally advanced rectal cancer management: a case report. Issue 9 (19th September 2022) - Edwards-Murphy, Amy; Earley, Helen; Creavin, Ben; McCullough, Peter; Cooke, Fiachra; Neary, Peter
Abstract: Treatment of locally advanced rectal cancer remains a challenge in colorectal surgery. It has had an evolving landscape over the past three decades. Implementation of total neoadjuvant therapy (TNT) as a novel approach to management has begun globally but long-term outcomes and data analysis to identify optimal schedules are eagerly awaited. We report a case of locally advanced rectal cancer management in a young male with a complete pathological response to TNT.